Flood Management Strategy in Samarinda City, East Kalimantan Province - Asha Mutiara Dimaputri; Faris Risyadi; Gigih Nur Putra Pratama; Mujahidin (Institute of Computer Science (IOCS), 2022)
Samarinda is the capital city of East Kalimantan Province. Geographically the location of Samarinda City is very strategic, thus making Samarinda a city of services, industrial trade and settlements with environmental insight. As the capital, the rapid urbanization and migration from other areas has spurred the development of settlements which tend to deviate from the concept of sustainable development without proper mitigation. This incident resulted in the frequency of flood disasters in Samarinda City being increasingly encountered by the public. The flood disaster hampers the traffic activities of people's lives and causes losses suffered by the community. The Samarinda City Government must pay attention and make efforts to improve and restore governance in flood control strategies. So that flooding in Samarinda City can be mitigated and prevented in order to create a flood-free on Samarinda City.This reasearch intends to formulate a strategy of flood control in the city of Samarinda using the theory of the strategy proposed by Bryson, with a qualitative descriptive ap- proach. Data collection through interviews and documentation.